Standing and Position of Islamic Law as Science in the Context of the Philosophy of Science (Study on the Tree of Rene Descartes Philosophy and the Loops of Knowledge Scheme of Gerald M. Edelman) - Adhiputro Pangarso Wicaksono (Universitas PGRI Madiun, 2022)
This study aims to find out the standing and position of Islamic law as a science in the context of the philosophy of science. Research conducted with normative method resulted in the finding that in Rene Descartes's philosophical tree scheme, Islamic law, in this case is that the Qur'an and Hadith (As-Sunnah) are “rainwater” that provides the source of life for the philosophical tree. The “rainwater” enters the soil and then